Satisfaction as a Strategic Link between the Organizational Environment and Innovation: A Systematic Literature Review in the Context of Modern Organizations - Basir, Abdul; Hamida, Hamida; Aminah, Hania (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to examine the role of job satisfaction as a mediator in the relationship between the organizational environment—specifically transformational leadership and organizational commitment—and employees' innovative behaviors. Using a systematic literature review (SLR) approach, this study analyzed 20 scientific articles published in the 2015–2024 range. The article selection process follows the PRISMA protocol, starting from the initial identification of 112 articles through the Scopus database, which is then filtered and supplemented with articles from other relevant sources until a total of 20 studies are obtained that are worth analysis. The results of the study show that transformational leadership consistently has a positive effect on innovative behavior and that this influence is significantly mediated by job satisfaction. Organizational commitment was also found to strengthen job satisfaction and indirectly contribute to innovation. However, few studies have placed these two psychological variables—job satisfaction and organizational commitment—in one unified mediation model. This study concludes that job satisfaction is an important strategic link in translating organizational structural influences into innovative behaviors. These findings contribute to the organizational innovation literature by highlighting the importance of the psychological dimension in the process of emerging innovation in the workplace, as well as opening up opportunities for further research in the context of strategic organizations in Indonesia.